Analysis of Customer Relationship Management In Influencing Customer Satisfaction And Loyalty of Bank Muamalat Indonesia In Tulungagung - Kiky Nia Lorenza; Dede Nurohman (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
The paper aims to determine effect customer relationship management through affecting customer satisfaction and loyalty of Bank Muamalat Indonesia in Tulungangung. The study used an associative-quantitative method. The primary data was obtained from the questionaire through Google Form and the secondary data was obtained from observing the office and bank websites. 100 customers of Bank Muamalat Indonesia in Tulungangung was chosen as sample. The data was processed by hypothesis test using IBM SPPS version 25. The results that (a) the customer relationship management has positive and significant effect on customer loyalty, (b) the customer relationship management has positive and significant effect on customer satisfaction, and (c) the customer satisfaction has positive and significant effect on customer loyalty.